An Evaluation of Factors Predisposing Building Elements to Variation in Nigeria - Babatunde, S.O.; Babalola, M.O.; Jagboro, G.O; Opawole, A. (Institute of Research and Community Outreach - Petra Christian University, 2013)
The construction industry has been consistently criticized for poor performance in attaining clients’ requirements. The study, thus, assessed the factors predisposing building elements to variation with a view to providing cost-design information that enhance construction project delivery, that is, on-time completion of project within budget. The building elements considered in this study include substructure, frame, upper floors, and roof. Data were collected using well-structured questionnaires administered on professionals in consulting firms, contracting firms, and client organizations in Lagos metropolis. Data analysis was done using descriptive and inferential statistics. The results of the analysis revealed nine factors through factor analysis that predispose substructure to variation, seven factors predispose frame, six factors predispose upper floors, and seven factors predispose roofs to variation during construction process in Nigeria.